Diseño de un sistema de iluminación con energía fotovoltaica para el instituto educativo María Montessori de la ciudad de Cúcuta (2021)
In the present degree work, the design of a lighting system for the María Montessori educational institution located in the city of Cúcuta on Av. 0 # 0-70N was carried out, by means of photovoltaic solar panels to replace the current lighting system based on conventional energies and in this way contribute to government policies on environmental protection and energy saving electrical. The work plan that was proposed for the fulfillment of the objectives was based on the following stages: energy study, recognition of the area of ​​influence, estimation of loads and state of the structure where the photovoltaic system was located. The results showed that the annual energy generated is equivalent to the electricity consumption of the Institute and, in addition, constitutes an alternative for the generation of energy, from the use of available spaces in the upper part of the building (plate). It is concluded that by implementing this photovoltaic system, the consumption of conventional electric energy would be reduced by 1.89 kW / day with a cost of $ 550 kW / h, recovering the investment in approximately 8 years.